Електронна структура та взаємочин атомового і магнетного порядків стопів з вузькими d-зонами - Репецький, С.П.; Татаренко, В.А.; Мельник, І.М.; Лень, Є.Г. (Успехи физики металлов, 2008)
В огляді представлено результати дослідження взаємочину атомового й магнетного порядків у стопах з вузькими d-зонами. Розглянуто основні теоретичні підходи до опису невпорядкованих стопів з сильними електронними кореляціями та визначено межі їх застосовности. Проаналізовано зв’язок зміни атомового й магнетного порядків таких стопів з перебудовою їхнього електронного енергетичного спектру. В обзоре представлены результаты исследования взаимного влияния атомного и магнитного порядков в сплавах с узкими d-зонами. Рассмотрены основные теоретические подходы к описанию неупорядоченных сплавов с сильными электронными корреляциями и определены границы их применимости. Проанализирована связь изменения атомного и магнитного порядков таких сплавов с перестройкой их энергетического спектра электронов. In the review, results of investigation of interplay of atomic and magnetic orders in alloys with narrow d-bands are presented. The basic theoretical approaches to a description of the disordered alloys with strong electron correlations are considered, and validity ranges of these approaches are outlined. The interplay between the changes of atomic and magnetic orders in such alloys and the realignment of their electron energy spectrum is analysed. gigantic values, substantially exceeding the corresponding typical values for bulk materials. As revealed within the scope of the dipole approximation, the giant optical absorption cross sections in the quasi-zero-dimensional nanosystems provide a possibility to use these nanosystems as new efficient absorbing materials.